Pengaruh Penambahan Ubi Jalar Kuning (Ipomoea Batatas L.) dan Bunga Rosella (Hibiscus Sabdariffa L.) Terhadap Karakteristik Fisikokimia dan Organoleptik Saus Tomat - Fatin, Naila Salsabila Nurul; Saati, Elfi Anis; Anggriani, Rista (Food Technology and Halal Science Journal, 2024)
Abstract. Tomato sauce is a product produced from a mixture of tomato puree or tomato paste or tomato solids obtained from ripe tomatoes, which is processed with spices, with or without the addition of other food ingredients and permitted food additives. The addition of yellow sweet potato was chosen as a natural thickener and rosella flowers to replace the role of synthetic dyes in tomato sauce. The research design used in this study was a randomized factorial block design consisting of 2 factors, namely the addition of yellow sweet potato (0%,15% and 30%) and the addition of rosella flowers (0%, 5% and 10%). Parameters tested are water content, total dissolved solids, pH, total carotene, antioxidant activity, color intensity and organoleptic. The results showed that there was an interaction between the addition of yellow sweet potato and rosella flower on water content, total dissolved solids, pH, antioxidant activity. The addition of yellow sweet potato affected the water content, total dissolved solids, pH, total carotene, antioxidant activity, brightness (L) and redness (a+). The addition of rosella flowers affected the water content, total dissolved solids, pH, total carotene, antioxidant activity and brightness (L). The best treatment was A2B1 with a value of water content (63.32%), total dissolved solids (19.33°Brix), pH (3.89), total carotene (22.32µg), antioxidant activity (76.71%), color intensity (L 39.63; a* 15.6; b* 16.2); aroma 4.24 (rather delicious), color 4.12 (rather bright), taste 4.56 (delicious), texture 4.88 (thick), preference 4.36 (rather like).